Pan-Cancer Analysis Shows That ALKBH5 Is a Potential Prognostic and Immunotherapeutic Biomarker for Multiple Cancer Types Including Gliomas - Wei, Cheng; Wang, Bo; Peng, Dazhao; Zhang, Xiaoyang; Li, Zesheng; Luo, Lin; He, Yingjie; Liang, Hao; Du, Xuezhi; Li, Shenghui; Zhang, Shu; Zhang, Zhenyu; et al. (Frontiers in Immunology, 2022)
Background: AlkB homolog 5 (ALKBH5) is a N6-methyladenosine (m6A) demethylase associated with the development, growth, and progression of multiple cancer types. However, the biological role of ALKBH5 has not been investigated in pan-cancer datasets. Therefore, in this study, comprehensive bioinformatics analysis of pan-cancer datasets was performed to determine the mechanisms through which ALKBH5 regulates tumorigenesis. Methods: Online websites and databases such as NCBI, UCSC, CCLE, HPA, TIMER2, GEPIA, Oncomine, cBioPortal, UALCAN, STRING, MEXPRESS, LinkedOmics, SangerBox, ImmuCellAl, xCell, and GenePattern were used to extract data of ALKBH5 in multiple cancers. The pan-cancer patient datasets were analyzed to determine the relationship between ALKBH5 expression, genetic alterations, methylation status, and tumor immunity. Targetscan, miRWalk, miRDB, miRabel, LncBase, and metascape databases were used to identify microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) that regulate expression of ALKBH5 and construct the lncRNA-miRNA-ALKBH5 network. In vitro CCK-8, wound healing, and Transwell assays as well as in vivo xenograft animal experiments were performed to determine the biological functions of ALKBH5 in glioma cells. Results: The pan-cancer analysis showed that ALKBH5 was upregulated in several solid tumors. ALKBH5 expression significantly correlated with the prognosis of cancer patients. Genetic alterations including duplications and deep mutations of the ALKBH5 gene were identified in several cancer types. Alterations in the ALKBH5 gene correlated with tumor prognosis. Methylation of the ALKBH5 promoter was reduced in various tumor tissues compared to corresponding normal tissues. ALKBH5 expression correlated with the expression of immune checkpoint (ICP) genes, and influenced sensitivity to immunotherapy. GO and KEGG enrichment analyses showed that ALKBH5-related genes were enriched in the inflammatory, metabolic, and immune signaling pathways. We constructed a lncRNA-miRNA network that regulates ALKBH5 expression in tumor development and progression. In vitro and in vivo experiments showed that ALKBH5 promoted proliferation, migration, and invasion of glioma cells. Conclusions: ALKBH5 was overexpressed in multiple cancer types and promoted the development and progression of cancers through several mechanisms including regulation of the tumor-infiltration of immune cells. Our study shows that ALKBH5 is a promising prognostic and immunotherapeutic biomarker in some malignant tumors.